Acquisition, Retention, and Recall of Memory After Injection of RS67333, a 5-HT4 Receptor Agonist, Into the Nucleus Basalis Magnocellularis of the Rat - Orsetti, Marco (Cold Spring Harbor Laboratory Press, 2003)
The serotonin 5-HT4 subtype receptor is predominantly localized into anatomical structures linked to memory and cognition. A few experimental studies report that the acute systemic administration of selective 5-HT4 agonists has ameliorative effects on memory performance, and that these effects are reversed by contemporary administration of 5-HT4 receptor antagonists. To verify whether this procognitive action occurs via the activation of the cholinergic nucleus basalis magnocellularis (NBM)-cortical pathways, we examined the effects of RS67333, a selective partial agonist of the 5-HT4 receptor, on rat performance in a place recognition task upon local administration of the drug into the NBM area. The intra-NBM administration of RS67333 enhances the acquisition (200–500 ng/0.5 μL) and the consolidation (40–200 ng/0.5 μL) of the place recognition memory. These effects are reversed by pretreatment with the selective 5-HT4 receptor antagonist RS39604 (300 ng/0.5μL). Conversely, the recall of memory is not affected by the 5-HT4 agonist. Our results indicate that 5-HT4 receptors located within the NBM may play a role in spatial memory and that the procognitive effect of RS67333 is due, at least in part, to the potentiation of the activity of cholinergic NBM-cortical pathways.